2015
DOI: 10.1371/journal.pone.0119060
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Free-Ranging Wild Boar (Sus scrofa) in the Re-Emergence of Enzootic Pneumonia in Domestic Pig Herds: A Pathological, Prevalence and Risk-Factor Study

Abstract: Enzootic pneumonia (EP) caused by Mycoplasma hyopneumoniae has a significant economic impact on domestic pig production. A control program carried out from 1999 to 2003 successfully reduced disease occurrence in domestic pigs in Switzerland, but recurrent outbreaks suggested a potential role of free-ranging wild boar (Sus scrofa) as a source of re-infection. Since little is known on the epidemiology of EP in wild boar populations, our aims were: (1) to estimate the prevalence of M. hyopneumoniae infections in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 81 publications
1
14
1
Order By: Relevance
“…23,000 km 2 ), of which a large part reaches altitudes above the timber line, and iv) the part of Ticino located south from the Alps (approx. 2,812 km 2 ); (4) covering most of the Swiss border to France, Germany and Italy; and (5) complementing former studies on wild boar pathogens in Switzerland [ 77 , 78 ]. Contacts are possible among wild boar in the study units A-D (i.e., northern population) whereas wild boar in study unit E (Ticino, i.e., southern population) are separated from the northern population by the Alps and can only interact with Italian wild boar populations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…23,000 km 2 ), of which a large part reaches altitudes above the timber line, and iv) the part of Ticino located south from the Alps (approx. 2,812 km 2 ); (4) covering most of the Swiss border to France, Germany and Italy; and (5) complementing former studies on wild boar pathogens in Switzerland [ 77 , 78 ]. Contacts are possible among wild boar in the study units A-D (i.e., northern population) whereas wild boar in study unit E (Ticino, i.e., southern population) are separated from the northern population by the Alps and can only interact with Italian wild boar populations.…”
Section: Methodsmentioning
confidence: 99%
“…Calculation of the target sample size per hunting season and study unit was derived from the regional hunting bags and performed with the WinEpiscope 2.0 software package. Since 2011 samples sizes have been calculated with the aim of estimating prevalence and assuming a prevalence of 50 %, with a confidence level of 95 % and an accepted absolute error of 5 % [ 78 ]. Efforts were made towards an even age and sex distribution among units.…”
Section: Methodsmentioning
confidence: 99%
“…EP-like lesions normally appear as a purple or gray area of pulmonary consolidation of the cranioventral lobes [ 58 ]. The appearance of the lesions depends on the stage of the disease: damaged lobes are swollen in the acute stage of the disease, while in the chronic phase, interlobular scarring tissue is typically present [ 59 ].…”
Section: Pluck Lesionsmentioning
confidence: 99%
“…These animals have been identified as potential sources of African swine fever virus [56,73,84], Aujeszky's disease [78,79], brucellosis [78,79,82], Campylobacter [80], classical swine fever [85], giardiasis [80], salmonellosis [81], Streptococcus suis [77], toxoplasmosis [81,82], trichinellosis [61,82], tuberculosis [86,87], and yersiniosis [81] in domestic animals, and leptospirosis, tuberculosis, hepatitis E, brucellosis, and trichinellosis in humans [56,78,83]. Conversely, Batista Linhares et al indicated greater probability of contagion of enzootic pneumonia caused by Mycoplasma hyopneumoniae from domestic pigs to wild boars [88]. Pathogens can also be transmitted through consumption of contaminated meat, as in the case of bacteria such as Escherichia coli, Listeria monocytogenes, and Campylobacter [80,81] or viruses such as African swine fever [73] and classic swine fever [85].…”
Section: Wild Boarmentioning
confidence: 99%